Comparative study of P-doped and undoped ZnO Nanostructures using thermal evaporation and vapor transport method - Al-Azri, K.; Nor, R.M.; Amin, Y.M.; Al-Ruqeishi, M.S. (2012)
We report the synthesis of phosphorus-doped (P-doped) and undoped ZnO nanostructures using a thermal evaporation and vapor transport on Si(100) substrate without any catalyst and at atmospheric argon pressure. The structural and optical properties of P-doped ZnO nanostructures and undoped ZnO nanostructures have been extensively investigated using filed emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and Photoluminescence (PL). FESEM observation reveals that the morphology of ZnO nanostructures was changed from a hexagonal-like shape to a spherical shape when doping with P. While, XRD results indicate that P-doped ZnO nanostructures lost the (002) orientation preference and became randomly oriented. In addition, shifting of (002) diffraction peak has been found due to the incorporation of P into ZnO. Room temperature (PL) spectrum of P-doped ZnO nanostructures shows a high efficiency of green emission which was attributed to the presence of phosphorus atoms in the ZnO nanostructures. Â© 2012 Penerbit UTM Press. All rights reserved.